The influence of zakat, Human Development Index, open unemployment rate, and income on poverty in Indonesia - Mutmainah, Siti; Rahayu, Nurul Widwayati Islami; Fauzan, Fauzan; Sholichin, Agil Amirus (Universitas Islam Indonesia, 2024)
IntroductionIn Indonesia, poverty is influenced by a complex set of economic, social, and structural factors. Issues such as economic crises, increasing populations, income levels, long-term unemployment, health problems, low educational background, limited access to goods and services, geographical location, and gender contribute to poverty.ObjectivesThis study aims to analyze the impact of zakat, the Human Development Index (HDI), the open unemployment rate, and income on poverty in Indonesia from 2013 to 2022.MethodThis study used quantitative methods with multiple linear regression analysis using Eviews. Time-series data were sourced from Statistics Indonesia (Badan Pusat Statistik) and the National Amil Zakat Agency (Badan Amil Zakat Nasional). The analysis includes classical assumption tests such as normality, multicollinearity, heteroscedasticity, and autocorrelation tests.ResultsThe findings reveal that zakat, HDI, and income have negative and significant impacts on poverty in Indonesia. This indicates that increases in zakat, HDI, and income lead to reductions in poverty levels. However, the open unemployment rate did not have a significant effect on poverty.ImplicationsThe results highlight the importance of zakat as a socioeconomic tool to reduce poverty by redistributing wealth. Improving human development through better education, healthcare, and economic opportunities is crucial for alleviating poverty. Policies aimed at increasing income levels can significantly reduce poverty rates.Originality/NoveltyThis study contributes to the literature by examining the simultaneous effects of zakat, HDI, the open unemployment rate, and income on poverty across Indonesia, offering insights into effective poverty reduction strategies.